Heart rate variability and its modulation by nutrients: a narrative review on implications for cardiovascular aging - Zhao, Youyou; Chen, Peng; Zhang, Yongxin; Huo, Shaofeng; Yu, Danyang; Zeng, Xinyi; Zhang, Weiguo (Frontiers in Neuroscience, 2025)
Altered intercellular communication is a hallmark of aging, influencing systemic processes across the cardiovascular, neurological, and psychological systems. Among these, cardiovascular aging is particularly important due to its strong association with morbidity and mortality in industrialized societies. Heart rate variability (HRV) reflects the natural fluctuations in the time intervals between heartbeats and serves as an indicator of neural interorgan communication, particularly within the cardiac and neural systems, which is fundamentally underpinned by intercellular signaling. HRV captures the autonomic nervous system’s regulation of cardiac function, reflecting the balance between sympathetic and parasympathetic activity. Beyond its mechanistic significance, HRV provides a window into the organism’s adaptive capacity to stress and the maintenance of homeostasis, encapsulating the interplay between cardiovascular, neural, and endocrine systems. Increasing evidence recognizes HRV as a predictor of survival across diverse populations, from patients with cardiovascular, metabolic, and neurological disorders to the general population. Importantly, HRV is modifiable, making it a compelling target for interventions aimed at enhancing healthspan and lifespan. Among these interventions, nutritional strategies hold particular promise. This review synthesizes current evidence on the impact of key dietary factors including omega-3 fatty acids, vitamin B12, and calorie restriction on HRV modulation in human studies. These findings underscore the potential of nutritional approaches to mitigate the deleterious effects of cardiac and neural aging while promoting systemic resilience. HRV transcends its role as a biomarker, serving both as an independent outcome measure and a critical component of algorithmic models for evaluating the efficacy of aging-related interventions. By advancing our understanding of HRV and its modulation through diet, this review bridges fundamental aging biology with applied clinical strategies, highlighting its transformative potential in optimizing both quality of life and longevity.